Pemanfaatan Media Sosial Tiktok Untuk Memfasilitasi Maharah Kalam - Randy Randy (CV. SINAR HOWUHOWU, 2026)
This literature review investigates the use of TikTok social media as a medium to facilitate maharah kalam (Arabic speaking skills). TikTok's short-video format, integrated with audio-visual features, interactive comment sections, and algorithmic content distribution, presents novel affordances for language learning. This study applies a systematic literature review methodology, analyzing 22 research articles and relevant documents published between 2019 and 2024 from international and national academic databases. The findings reveal that TikTok supports maharah kalam development through three primary mechanisms: (1) exposure to authentic spoken Arabic through native speaker content; (2) active production of spoken Arabic via video creation and participation in language challenges; and (3) social interaction and peer feedback through comments and duet features. Studies also indicate that TikTok significantly enhances learner motivation, reduces speaking anxiety, and promotes a sense of authentic communicative purpose. Nevertheless, challenges such as superficial linguistic content, lack of structured learning guidance, potential distraction, and limited access to quality Arabic-language educators on the platform remain concerns. This review recommends that Arabic language instructors in Indonesia strategically incorporate TikTok as a complementary tool within task-based and project-based learning frameworks.